Factors affecting turnover of nurses in rural clinics of Lesotho - Matamane, Sekhametsi (University of the Free State, 2014)
The primary objective of the study was to establish the factors affecting turnover of nurses at the nine rural clinics in Lesotho that are managed by the Lesotho Flying Doctors Services. The turnover of nurses at the nine rural clinics of Lesotho has contributed to challenges faced by the health care system of the country. This is exacerbated by the high prevalence of HIV and AIDS that has led to a heavier burden on nurses to provide anti-retroviral treatment and primary health care. The widespread poverty dominant in the rural areas affected a large number of Basotho to use public health care as opposed to private health care. In addition, low remuneration and hardship allowances paid to nurses in the rural areas may drive them to look for better paying jobs. Challenges faced by the health college are aggravating the situation. Using the qualitative research method, the study concluded that demographic factors have varying effects on the turnover of nurses. However, their influence is less significant in comparison with general factors and economic factors. Among other factors identified in the three themes, the participants were dissatisfied with accommodation, which was very poor despite the recent refurbishment and construction of the clinics. It appears from the findings that non-financial factors were more significant than the financial ones, and many participants were concerned about a number of them. The most significant non-financial factors, for example, include the issue of accommodation, communication, and infrastructure, which in turn affect access to the remote clinics negatively. Economic factors had a significant effect on the turnover of nurses, and the main challenges were caused by budgetary constraints. The turnover of nurses, particularly with regard to those working in the rural areas, can affect the quality of services in the nursing profession negatively. A number of factors, consequences, and challenges may also hamper nurses‟ work at the remote clinics. Management at the Ministry of Health should implement a number of strategies that will assist in reducing the level of turnover of nurses and enhance health care services at the rural clinics.
Dissertation (MBA (Business Administration)) --University of the Free State, 2014
Keywords: Turnover; Shortage; Nurses; Job satisfaction; Infrastructure; Communication; Financial and budgetary constraints; Demographic and economic factors